The Welsh language in Patagonia: Evolution and adaptation. Issue 2 (October 2018) - Harris, Trevor
Abstract : It was in order to be able to continue speaking Welsh, unhindered by the British state, that Welsh colonists migrated to Patagonia, in the south of Argentina. But the Welsh community soon came under the control of the expanding Argentine state. Respite for the Welsh-speaking community from interference by a powerful, centralised administration proved to be short-lived: what the Welsh had sought to escape from by leaving Britain, simply reappeared in the guise of the Argentine Republic. Relations between the Welsh colony and the government soured, especially from the 1880s until the turn of the century. Second generation Welsh colonists were, of necessity, increasingly bilingual, as Spanish became the official language of Argentina's fast-growing, multi-ethnic population. The Welsh colony's schools and local institutions allowed linguistic resistance for a time, as did the written press which had grown up with the settlement. The Welsh, however, found themselves in a very difficult position, instrumentalised as – ironically – an "Anglo-Saxon" constituent of Argentina's Eurocentric immigration policy, and opposed as a troublesome linguistic minority to be assimilated in the same manner as the native Indian tribes. Trapped in this way, the colony's own language policy further evolved. English was reappropriated by inhabitants of the Welsh colony who preferred to re-migrate, often to dominions of the British Empire: notably, Canada and Australia. From the inter-war period on, there was therefore a real danger that Welsh might die out in Patagonia, reduced as it was to domestic use. But a revival was prompted by the rise of Welsh nationalism, especially by devolution in the late 1990s and within the favourable context created by the European Union support for linguistic diversity, by the Council of Europe's Charter for Regional or Minority Languages and by the vigorous language policy of the Welsh National Assembly. This revival has been actively supported by the British Council's "Welsh Language Project".